RELATIONSHIP OF HEMOGLOBIN CONCENTRATION AND LUNG VITAL CAPACITY WITH MAXIMAL AEROBIC CAPACITY (VO2 MAX) AT INDONESIAN NATIONAL ATHLETES - Junaidi Junaidi (Program Pascasarjana Universitas Negeri Jakarta, 2018)
The objectives of this research are to obtain information the relationship of hemoglobin concentration and lung vital capacity with VO2 max at Indonesian national athletes either separately or together. This study was conducted at Indonesian national athletes by using survey method with regression and correlation techniques analysis. The number of 50 athletes from 550 populations as a sample is selected purposive random sampling, The research findings there are 1). There is a relationship of hemoglobin concentration with VO2 max, equation of regression ,used T test (Î±= 0,05), tvalue = 10,25, ttable = 2,00, correlation coefficient ; rxy1=0,719 and determinant coefficient (r2) = 0,517, 2). There is a relationship of lung vital capacity with VO2 max, equation of regression , used T test (Î±= 0,05), tvalue = 7,48, ttable = 2,00, correlation coefficient; rxy2=0,733 and determinant coefficient (r2) = 0,538 , 3). There are a relationship of hemoglobin concentration and lung vital capacity are together with VO2 max, equation of regression , used T test (Î±= 0,05), tvalue = 87,28, ttable =1,59, correlation coefficient ry1-2 = 0,734 and determinant coefficient(ry1-2) = 0,539 Keywords; Hemoglobin concentration, lung vital capacity and VO2 max